Analysis of factors influencing casual sexual behavior among male college students in Zhejiang Province, China. - Zhongrong Yang; Weiyong Chen; Meihua Jin; Wanjun Chen; Lin Chen; Xin Zhou (PLoS ONE)
Objective The purpose of this study was to explore the situations and factors influencing casual sexual behavior among male college students, in order to provide scientific evidences and measures of the prevention and control for HIV/AIDS. Method Using the stratified cluster sampling method, male college students who self-reported sexual behavior were selected as survey subjects in 13 colleges and universities in 11 cities of Zhejiang Province from October to November 2018. We used a custom online questionnaire to collect information on the demographic characteristics, sexual attitudes, sexual behaviors, and HIV interventions of the respondents. The χ2 test was performed on the composition ratios between different groups. With the occurrence of casual sexual behavior as the dependent variable, logistic regression was used to analyze the factors influencing casual male sexual behavior. Results A total of 2734 male college students were surveyed, aged 20.20±1.41 years, of which 595 had casual sex, accounting for 21.7%. The rate of HIV prevention awareness among the participants was 85.1%. Multivariate analysis showed that receiving a self-assessment of HIV risk conducted by the school (Ajusted OR = 1.45, 95% CI = 1.14-1.84), knowing that HIV self-test kits were available at school (Ajusted OR = 2.02, 95% CI = 1.56-2.62), accepting one-night stands (Ajusted OR = 2.82, 95% CI = 2.18-3.66), accepting commercial sex (Ajusted OR = 1.95, 95% CI = 1.53-2.48), being a man who has sex with men (Ajusted OR = 1.81, 95% CI = 1.37-2.39), being a senior (Ajusted OR = 0.46, 95% CI = 0.30-0.71), having knowledge of HIV/AIDS prevention and treatment (Ajusted OR = 0.66, 95% CI = 0.51-0.86), and knowing that the CDC provides HIV testing services (Ajusted OR = 0.56, 95% CI = 0.41-0.77) were factors influencing male college students' casual sexual behavior. Conclusion Male college students who have causal sexual behaviors have a high degree of openness in sexual attitudes, insufficient knowledge of AIDS prevention, and knowledge of HIV testing-related information but low testing rates. For male college students' HIV prevention education intervention, it is necessary to emphasize the establishment of correct sexual attitudes and concepts and promote safe sexual behaviors to prevent the spread of HIV.